2010
DOI: 10.2355/isijinternational.50.231
|View full text |Cite
|
Sign up to set email alerts
|

As-cast Austenite Grain Structure in Al Added 0.2 wt% Carbon Steel

Abstract: Figure 3 shows a phase diagram of Fe-0.2wt%C-0.035wt%P-0.8wt%Mn-0.2wt%Si-0.006wt%N-xAl system calculated from CALPHAD method. 14) We employed the thermodynamic database, PanIron for all the calculations. 15) The horizontal axis is Al concentration. The liquidus temperature does not substantially change with the Al concentration. It should be noticed that the type of steel changes from hyperperitectic to hypoperitectic one at 0.53 wt% Al. When Al concentration is less than 0.53 wt%, the solidus temperature, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…As was consistent with our previous study on the effects of Al addition, 14) the present EPMA analysis showed that the AlN particles did not exist in the samples with 0.04 and 0.1 mass% Al, and they were rarely dispersed in the samples with 0.54 and 1.04 mass% Al. Consequently, the AlN should not be responsible for the refinement described in Fig.…”
Section: Effects Of Simultaneous Additions Of Al and P Onsupporting
confidence: 80%
See 3 more Smart Citations
“…As was consistent with our previous study on the effects of Al addition, 14) the present EPMA analysis showed that the AlN particles did not exist in the samples with 0.04 and 0.1 mass% Al, and they were rarely dispersed in the samples with 0.54 and 1.04 mass% Al. Consequently, the AlN should not be responsible for the refinement described in Fig.…”
Section: Effects Of Simultaneous Additions Of Al and P Onsupporting
confidence: 80%
“…In our previous study, we investigated the effects of Al addition on the as-cast g grain structure in 0.2 mass% C steel. 14) It was observed that the Al addition leads to the refinement of the g grain structure obtained by permanent mold casting. The g grain structure consisted of Coarse Columnar Grain (CCG), Fine Columnar Grain (FCG) and Coarse Equiaxed Grain (CEG) regions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the decrease in Tγ corresponds to a decrease in the temperature for onset of rapid grain growth, thereby retarding γ grain growth at high temperatures. In fact, it has been reported in several studies [2][3][4][5] that reduction of Tγ by alloying element addition leads to grain refinement of as-cast γ structure. It should be noted that these early works focused on the reduction of Tγ due to stabilization of liquid or δ phase in a low temperature region.…”
Section: Introductionmentioning
confidence: 99%